DAMPAK PEMEKARAN DAERAH TERHADAP PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN DI KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Putri, Wilistia Dwi; ., Turtiantoro; H., Nunik Retno (Journal of Politic and Government Studies, 2016)
This study is based on the growing phenomenon of regional expansion rolling after the reform in Indonesia. Where this is a manifestation of democratization that has been formed a lot of New Autonomous Region (NAR). However, there are still a lot of controversy in this regard. Including the public services that is still far from good. In fact, the public service is one of the objectives of regional expansion in improving the welfare of society. Meranti Islands District is a NAR expansion result, which was inaugurated in 2009 and was chosen as a focus area of research. Therefore, the focus of the problem in this research is the public service field of population administration before and after becoming a NAR along with the constraints encountered in service after becoming a NAR.This study aims to clarify the public service in Meranti Islands regency of Riau Province population administration, before and after becoming a NAR and obstacles faced in the public service in Meranti Islands regency of Riau Province population administration after becoming NAR. The method used is descriptive qualitative which will present the data in accordance with the findings and facts on the field.The results showed that the regional division in Meranti Islands District is based on the aspirations of the people that have been developed previously. After becoming a NAR, the Government had stints in accordance with the applicable rules but still was some obstacles appeared in the population administration public service. Issue like this should be in the government's attention on regional expansion's goal, which is public service improvement could be achieved considering the control range of the government has been more narrow.Keywords: Region Expansion, NAR, Public Services